Legalitas Kegiatan Badan Usaha Koperasi Simpan Pinjam di Kabupaten Batang Hari - Ngaliya, Chofifatun; Muskibah, Muskibah; Naili Hidayah, Lili (Universitas Jambi, Fakultas Hukum, 2026)
Cooperatives are basically business activities from members for members. One type of cooperative business activity is the Savings and Loans Cooperative. This research is motivated by the large number of Cooperatives in Batang Hari Regency but many of them do not fulfill the legality aspects, one of which is the Manunggal Jaya Savings and Loans Cooperative, Muara Tembesi branch in Penerokan Village, Bajubang District, Batang Hari Regency which is engaged in the Savings and Loans business, but in practice the Cooperative does not fulfill the legality aspects of the Deed of Establishment, legal entity status, permits, Business Identification Number (NIB), Annual Member Meeting (RAT), and Articles of Association/Bylaws. Missing stairs. This research aims to find out the legality of the Manunggal Jaya Savings and Loans Cooperative business entity and the implications of activities that do not meet legal aspects for borrowers. The research method used is empirical juridical research, namely research that prioritizes empirical data from the field to determine the application of law in society. The results of this research are that the Savings and Loans Cooperative in practice carries out legal activities because it does not fulfill the legality aspects of the Cooperative, so the activities carried out do not have valid legal status. And the implications of not fulfilling legal aspects have a direct impact on borrowers who do not know the legal status of the Cooperative.